Real‐time stability assessment in smart cyber‐physical grids: a deep learning approach. Issue 4 (27th May 2020) - Darbandi, Farzad; Jafari, Amirreza; Karimipour, Hadis; Dehghantanha, Ali; Derakhshan, Farnaz; Raymond Choo, Kim‐Kwang
Abstract : The increasing coupling between the physical and communication layers in the cyber‐physical system (CPS) brings up new challenges in system monitoring and control. Smart power grids with the integration of information and communication technologies are one of the most important types of CPS. Proper monitoring and control of the smart grid are highly dependent on the transient stability assessment (TSA). Effective TSA can provide system operators with insightful information on stability statuses and causes under various contingencies and cyber‐attacks. In this study, a real‐time stability condition predictor based on a feedforward neural network is proposed. The conjugate gradient backpropagation algorithm and Fletcher–Reeves updates are used for training, and the Kohonen learning algorithm is utilised to improve the learning process. By real‐time assessment of the network features based on the minimum redundancy maximum relevancy algorithm, the proposed method can successfully predict transient stability and out of step conditions for the network and generators, respectively. Simulation results on the IEEE 39‐bus test system indicate the superiority of the proposed method in terms of accuracy, precision, false positive rate, and true positive rate.